Stratification and dynamics of microbial loop communities in Lake Fryxell, Antarctica - Roberts, EC; Laybourn-Parry, J; McKnight, DM; Novarino, G (Freshwater Biology, 2000)
1. Lake Fryxell, situated in the McMurdo Dry Valleys, Antarctica, offers the opportunity to study microbial loop processes in the absence of crustacean zooplankton and other higher organisms. This is the first study of Lake Fryxell to provide detailed temporal and vertical variations of microbial loop organisms. 2. Protozoan communities are concentrated around the chemocline (9-10 m) in Lake Fryxell. Phototrophic nanoflagellates (PNAN), heterotrophic nanoflagellates (HNAN) and ciliates formed deep maxima of 14580, 694 and 58 cells mL-1 respectively. Although abundance and biomass at the chemocline was high, diversity of protozoa was low, Plagiocampa accounting for > 80% of the total ciliate biomass. 3. In the mixolimnion (4.5-8 m), protozoa were less abundant, but more diverse, with 24 ciliate morphotypes being identified within this region of the water column. Inter-annual variability of protozoan biomass and abundance was greater in the mixolimnion than at the chemocline due to more variable nutrient and prey concentrations. 4. Physicochemical gradients in Lake Fryxell were very stable because the perennial ice cover reduced wind driven currents. As a consequence, ciliate species occurred in distinct depth strata, Monodinium being most abundant directly beneath the ice cover, Askenasia having maximum abundance at 8 m and Plagiocampa dominating ciliate biomass at the chemocline. The lack of vertical mixing reduced seasonal successions of PNAN and ciliate species. Three cryptophyte species dominated the PNAN community at all times (> 79% of total biomass).